Perancangan Sistem Informasi Reservasi Hotel Graha Dewata Juwana Menggunakan Layanan Web Service - PD, IGK Indra; Somantri, Maman; Satoto, Kodrat Iman (Transmisi, 2012)
Hotel management business is one that is promising for entrepreneurs. However, such businesses are more suitable for middle and upper towns where the business climate is promising. For businessmen hotel located in the scope of a small town, this kind of business is a gamble that one-one could bankrupt. Typically, the campaign conducted in the hotel in a small town is done by word of mouth. Research is underway to create a program application for reservation. As one solution, the internet media is a solution that feels right. Where present, internet access is getting cheaper, easier and faster. Which is sufficient to help a particular hotel in a small town, in promoting themselves and show their existence. Web service as one of the services used, for this hotel information systems in the future can be developed according to the needs of the hotel. As in the integration with other systems that use different programming languages​​. The study produced for the application program in the form of hotel bookings website. The results obtained are in the form of hotel reservation information system that provides information on the number of rooms available. Given this system, will help users outside the city to find out information about places to stay are. In addition, this application can also provide information rooms that can be used on a specific date according to the time we want. Keywords: hotel, reservation